Challenges with international normalised ratio control in paediatric patients with rheumatic heart valve replacement surgery in the Eastern Cape Province, South Africa - Makrexeni, ZM (SA Heart Journal, 2025)
Introduction: Rheumatic heart disease (RHD) is a preventable chronic condition that affects the heart valves. The incidence of acute rheumatic fever (ARF) and RHD has waned in Western countries; however, this is not the case in developing countries. Poor access to healthcare and a lack of adherence to international normalised ratio (INR) monitoring in RHD contribute to thromboembolic complications. Methods: Records of patients from the Eastern Cape municipal districts with RHD were reviewed over 10 years. Patients who underwent rheumatic valve replacement surgery were isolated and analysed for their INR control. Results: A total of 30 patients with RHD were reviewed. All patients presented with severe RHD. Of the 30 patients, 20 had mitral valve replacement surgery, and 6 had mitral valve repair surgery. The 6 patients who had mitral valve repair surgery eventually required mitral valve replacement. Those who had mitral valve replacement surgery were started on anticoagulation (warfarin) post-operatively. Two patients died due to mitral valve thrombosis. Four patients were subsequently admitted for anticoagulation due to a thrombosed prosthetic mitral valve. Most of the patients were struggling to maintain a therapeutic range INR with values ranging from 1.1 to 2, and up to 8–10 on rare occasions. Conclusion: Most chronic RHD patients underwent mitral valve replacement surgery with a prosthetic valve. Most patients who were started on warfarin struggled to maintain a therapeutic range INR postoperatively due to poor healthcare access and adherence. Keywords: acute rheumatic fever, rheumatic heart disease, valve replacement surgery, international normalised ratio, disease outcomes